Hierarchical self-assembly of enantiopure and racemic helicenes at the liquid/solid interface: from 2D to 3D. Issue 45 (14th November 2017) - Cao, Hai; Minoia, Andrea; De Cat, Inge; Seibel, Johannes; Waghray, Deepali; Li, Zhi; Cornil, David; Mali, Kunal S.; Lazzaroni, Roberto; Dehaen, Wim; De Feyter, Steven
Abstract : The many ways helicenes assemble at the molecular level eventually evolve into complex crystalline forms on a macroscopic scale. Abstract : The performance of organic nanostructures is closely related to the organization of the functional molecules. Frequently, molecular chirality plays a central role in the way molecules assemble at the supramolecular level. Herein we report the hierarchical self-assembly of benzo-fused tetrathia[7]helicenes on solid surfaces, from a single surface-bound molecule to well-defined microstructures, using a combination of various characterization techniques assisted by molecular modeling simulations. Similarities as well as discrepancies are revealed between homochiral and heterochiral aggregations by monitoring the hierarchical nucleation of helicenes on surfaces, where the impact of enantiopurity, concentration and adsorbate–substrate interaction on molecular organization are disclosed.